The Green Investment Intentions of Gen Z: The Moderating Role of Financial Knowledge in the Theory of Planned Behavior - Thapa, Bharat Singh; Kafle, Bidhan (Kshitiz Management Review, 2025)
This study investigates factors influencing green investment intention among Gen Z investors, focusing on how green investment knowledge moderates these factors. Using the Theory of Planned Behavior (TPB), it examines the impact of attitudes, subjective norms, and perceived behavioral control on sustainable investment decisions. A survey of 385 purposively selected Gen Z investors provided demographic data and key study variables. Structural Equation Modeling (SEM) with Smart-PLS 4.1 analyzed relationships among green investment knowledge, attitudes, subjective norms, perceived behavioral control, and investment intention. Results reveal that attitude and perceived behavioral control significantly influence green investment intentions, whereas subjective norms do not. Green investment knowledge enhances the impact of attitudes on intentions but does not significantly moderate subjective norms or perceived behavioral control. These findings emphasize the importance of knowledge in fostering positive attitudes toward sustainable investments while suggesting that social influences and perceived control are less critical. The study highlights the need for financial literacy initiatives and awareness campaigns to encourage sustainable investment behaviors. It offers valuable insights for policymakers, financial institutions, and educators aiming to promote green investments and contributes to academic literature on knowledge’s role in green investment decisions, particularly in emerging economies.